Modeling the dynamics and control of rehabilitative exoskeleton with robotic crutches. (12th April 2018) - Cohen, Adi; Or, Yizhar
Rehabilitative robotics is an area in the medical field, where one can see a variety of different robotic applications, one of which is the use of robotic exoskeleton in rehabilitation of paraplegics. Current developments are only able to support paraplegics at most and require manual operation of crutches by the patient. In order to overcome this limitation, a theoretical model of a robotic device with actuated robotic crutches is proposed, which can be used to support people with high-level disability, such as quadriplegics who cannot use the existing solutions to perform walking gaits. This work presents kinematic trajectory planning of the proposed model and dynamic analysis of main movement stages. Finally, we present an open-loop control scheme that uses time scaling in order to track the desired joint trajectory of the under-actuated motion stage of crutch swinging. A simulated robotic model has also been developed using Simulink [version R2012b to R2014a]/SimMechanics ([version first generation] developed by Mathworks inc.) environment and has been used for verifying dynamic computations and simulating the robotic device movement under the open-loop control commands of joint torques.